Cost-effectiveness of a National Telemedicine Diabetic Retinopathy Screening Program in Singapore - Nguyen, Hai V.; Tan, Gavin Siew Wei; Tapp, Robyn Jennifer; Mital, Shweta; Ting, Daniel Shu Wei; Wong, Hon Tym; Tan, Colin S.; Laude, Augustinus; Tai, E. Shyong; Tan, Ngiap Chuan; Finkelstein, Eric A.; Wong, Tien Yin; et al. (Ophthalmology (Rochester, Minn.), 2016)
To determine the incremental cost-effectiveness of a new telemedicine technician-based assessment relative to an existing model of family physician (FP)–based assessment of diabetic retinopathy (DR) in Singapore from the health system and societal perspectives. Model-based, cost-effectiveness analysis of the Singapore Integrated Diabetic Retinopathy Program (SiDRP). A hypothetical cohort of patients aged 55 years with type 2 diabetes previously not screened for DR. The SiDRP is a new telemedicine-based DR screening program using trained technicians to assess retinal photographs. We compared the cost-effectiveness of SiDRP with the existing model in which FPs assess photographs. We developed a hybrid decision tree/Markov model to simulate the costs, effectiveness, and incremental cost-effectiveness ratio (ICER) of SiDRP relative to FP-based DR screening over a lifetime horizon. We estimated the costs from the health system and societal perspectives. Effectiveness was measured in terms of quality-adjusted life-years (QALYs). Result robustness was calculated using deterministic and probabilistic sensitivity analyses. The ICER. From the societal perspective that takes into account all costs and effects, the telemedicine-based DR screening model had significantly lower costs (total cost savings of S$173 per person) while generating similar QALYs compared with the physician-based model (i.e., 13.1 QALYs). From the health system perspective that includes only direct medical costs, the cost savings are S$144 per person. By extrapolating these data to approximately 170 000 patients with diabetes currently being screened yearly for DR in Singapore's primary care polyclinics, the present value of future cost savings associated with the telemedicine-based model is estimated to be S$29.4 million over a lifetime horizon. While generating similar health outcomes, the telemedicine-based DR screening using technicians in the primary care setting saves costs for Singapore compared with the FP model. Our data provide a strong economic rationale to expand the telemedicine-based DR screening program in Singapore and elsewhere.